Evaluation of serum sodium levels and mean platelet volume in children with community-acquired pneumonia - Amira Mohamed Hamed; Mohamed Fahmey Ibrahim; Hamada Kawshty Fayed; Mona Mohamed Abd EL-Meguid; Shimaa Esmail Hassen (Wolters Kluwer Medknow Publications, 2022)
Background and aim Community-acquired pneumonia (CAP) is one of the frequent causes of hospital admission, whereas hyponatremia (HN) is a common electrolyte abnormality in hospitalized patients and is associated with considerable morbidity and mortality. Mean platelet volume (MPV) may be a useful predictor for the diagnosis of CAP but not in disease severity. The purpose of this study was to evaluate serum levels of sodium and MPV in a child with CAP. Patients and methods This is a case-control study that has been carried out in a Malawi General Hospital. The total (100) participants included in the study were classified into two groups as follows: group I which is the case group included 50 children with clinical and laboratory evidence of pneumonia ranging from 1 month to 3 years. Group II which is the control group included 50 children (apparently healthy control) who attended for nonchest problem or serious medical condition. Serum sodium levels, hemoglobin levels, MPV, platelet count, total leukocyte count, and C-reactive protein were done to all children. Results HN was present in 82% of patients with CAP (41 out of 50). Patients with CAP had lower MPV than their healthy counterparts (7.11±0.42 vs. 9.14±1.04 fl; P<0.001). There was a statistically significant negative correlation between the grade of respiratory distress and the level of serum sodium and a positive correlation between the grade of respiratory distress and MPV (P<0.001). Conclusion HN is common among hospitalized children with CAP and MPV may be a useful predictor for the diagnosis of CAP.